(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
To assess the risk of developing type 2 diabetes mellitus (DM2) in patients with different risks of cardiovascular (CC) complications, as well as to identify the relationship between a high risk of DM2 and the main risk factors of CC.